Hubungan Status Gizi Ibu Hamil dengan Kejadian Abortus Spontan di Trimester Pertama - Treasa, Adisty Dwi; Arbiyah, Arbiyah; Hijrah, Hijrah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Spontaneous abortion is a common pregnancy complication in the first trimester. The causes are multifactorial, one of which is maternal nutritional status. Poor nutrition can affect embryo implantation and growth, increasing the risk of miscarriage. Objective: To determine the relationship between maternal nutritional status and the incidence of spontaneous abortion in the first trimester. Methods: This is an observational analytical study with a case-control approach. A purposive sample of 100 respondents was selected, consisting of 50 cases of spontaneous abortion and 50 women without abortion in the first trimester. Nutritional status was measured based on BMI and MUAC. Data were analyzed using the chi-square test with a significance level of 0.05. Results: There was a significant relationship between maternal nutritional status and the incidence of spontaneous abortion (p = 0.004). Mothers with poor nutritional status had a 3.2-fold higher risk of spontaneous abortion compared to mothers with normal nutritional status. Conclusion: Poor maternal nutritional status is positively correlated with an increased incidence of spontaneous abortion.